Pengaruh Sistem Perpajakan Dan Konflik Wajib Pajak Terhadap Penggelapan Pajak Dengan Probabilitas Pemeriksaan Pajak Sebagai Variabel Moderating Pada KPP Pratama Medan Timur - Sirait, Riris Marito; Anindya, Desy Astrid (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This paper aims to influence the taxation system and taxpayer conflict on tax evasion with the probability of tax audit as a moderating variable at KPP Medan Timur. The method used in this study is descriptive with a quantitative approach. The data of this study were obtained from questionnaires with functional auditors at KPP Pratama Medan Timur. The population of this study was the taxation system, taxpayer conflict, tax evasion, and the probability of tax audits. The number of samples used was 35 samples. The results of the study indicate that the variables: the taxation system has a positive and significant effect on increasing tax evasion at KPP Pratama Medan Timur, Thus, the taxpayer's economy has a positive and significant effect on tax evasion at KPP Pratama Medan Timur, and simultaneously, the taxpayer's collection and tax system together have a positive and significant effect on tax evasion at KPP Pratama Medan Timur, the possibility of tax audits is not a moderating variable.